A simple quantum-inspired bee colony algorithm for discrete optimisation problems. (1st January 2013) - Gao, Hongyuan; Li, Chenwan; Cui, Wen
To design a novel intelligence algorithm for discrete optimisation problem, a simple quantum-inspired bee colony algorithm (SQBCA) is proposed. The proposed SQBCA applies the quantum computing theory to bee colony optimisation (BCO), which is an effective discrete optimisation algorithm. Then the proposed simple quantum-inspired bee colony algorithm is used to solve benchmark functions and multiuser detection problems of code division multiple access (CDMA) system. By hybridising the bee colony optimisation and quantum computing theory, the quantum state and binary state of the quantum bees can be well evolved by simulated quantum rotation gate and simulated quantum not gate. The new robust multiuser detection based on SQBCA can search the global optimal solution. Simulation results for CDMA systems are provided to show that the proposed robust multiuser detection method is superior to the multiuser detection based on previous intelligence algorithms.